2021
DOI: 10.1093/tas/txab213
|View full text |Cite
|
Sign up to set email alerts
|

Intake, nutrient digestibility, rumen parameters, growth rate, carcase characteristics and cannabinoid residues of sheep fed pelleted rations containing hemp (Cannabis sativa L.) stubble

Abstract: The feeding value and impact of hemp stubble in the diet of ruminants is unknown. Fifteen Merino castrated male sheep were maintained in individual pens and fed one of three pelletised experimental inclusion diets, as a 0% (Control), 28% (Hemp 1), and 56% (Hemp 2) pellet that delivered a diet meeting the nutrient requirements of the animals. Inclusion of hemp stubble had no effect (P > 0.05) on either DM intake, live weight gain or the feed to gain ratio but positively impacted (P < 0.05) on nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This increase in antioxidant activity was also observed in milk of sheep fed HSC or hempseed (Mierliță, 2018), but not in the liver and meat of lambs fed 120 g/kg DM HSC replacing SBM (Antunović et al, 2020). The current study con rms that dietary bioactive phytochemicals (i.e., cannabinoids, tocopherols, and phenols and their metabolites) are transferred to and retained in ruminant tissues (Karaś et al, 2017;Krebs et al, 2021;Addo, 2022). To this end, the potential of these HSC bioactive phytochemicals to enhance goat production, meat health value and oxidative shelf life merit investigation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This increase in antioxidant activity was also observed in milk of sheep fed HSC or hempseed (Mierliță, 2018), but not in the liver and meat of lambs fed 120 g/kg DM HSC replacing SBM (Antunović et al, 2020). The current study con rms that dietary bioactive phytochemicals (i.e., cannabinoids, tocopherols, and phenols and their metabolites) are transferred to and retained in ruminant tissues (Karaś et al, 2017;Krebs et al, 2021;Addo, 2022). To this end, the potential of these HSC bioactive phytochemicals to enhance goat production, meat health value and oxidative shelf life merit investigation.…”
Section: Discussionsupporting
confidence: 51%
“…Hempseed cake contains several cannabinoids with cannabidiol (CBD, 3-170 µg/g) and cannabidiolic acid (CBDA, 4.4 µg/g) being the major ones, and no or negligible amounts of delta-9-tetrahydrocannabinol (THC) (Stastnik et al, 2020;Addo, 2022). Studies feeding diets containing HSC to cows (Addo, 2022) and hemp stubble to sheep (Krebs et al, 2021) reported little or no CBD in blood, liver, kidney, muscle, adipose tissue, urine and feces. However, even at low concentrations minor cannabinoids are able to exert antioxidant effects through synergistic interactions with other bioactive phytochemicals, a phenomenon known as the entourage effect (Andre et al, 2016;Russo, 2019; della Rocca and Di Salvo, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Data acquired in terms of the pH and concentration of the fermentation end products registered after 120 h of incubation are listed in Table 3 . The rumen pH, which depends mainly on diet characteristics and physiological condition ranges between 6.2 and 7.5 [ 47 ], was not modified by the extract addition, and no significant difference was observed among the different extract concentrations. Oskoueian et al [ 48 ], evaluating the effect of several flavonoids on the pH and ammonia nitrogen production, highlighted that the flavonoid addition did not alter these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the possible increase of protein digestibility and/or may to changes in the composition of the rumen bacteria population [ 61 ]. In fact, isobutyric and isovaleric acids are synthesized by rumen microorganisms via an oxidative deamination and an oxidative decarboxylation starting from the branched-chain amino acids, valine, and leucine, respectively [ 47 ]. Additionally, other studies observed that flavonoids, pure [ 48 , 62 ] or in a mixture [ 63 ], are able to improve VFAs production; the flavanone naringenin appeared to mainly increase acetate [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gas chromatography (GC) and liquid chromatography (LC) methods have been widely employed for the analysis of cannabinoids in cannabis and biological samples [14][15][16]. Recently, multiple research studies have been conducted to investigate the transfer of cannabinoids from hemp-related diets to livestock tissues and products [8,[17][18][19][20][21]. Several of these studies have observed the transfer of acidic cannabinoids from hemp feed to cattle blood plasma [8,17,18].…”
Section: Introductionmentioning
confidence: 99%